Explaining Christian origins and early Judaism : contributions from cognitive and social science - Luomanen, Petri, 1961-; Pyysiäinen, Ilkka.; Uro, Risto. (Biblical Interpretation Series, 2007)
Cognitive science of religion is a radically new paradigm in the study of religion. Apart from psychology and anthropology of religion, also historians of religion have shown increasing interest in this approach. This volume is groundbreaking in combining cognitive analysis with historical and social-scientific approaches to biblical materials, Christian origins, and early Judaism. The book is in four parts: an introduction to cognitive and social-scientific approaches, applications of cognitive science, applications of conceptual blending theory, and applications of socio-cognitive analyses. The book will be of interest for historians of religion, biblical scholars, and those working in the cognitive science of religion.